Comparison between intramuscular oxytocin versus oxytocin with sublingual misoprostol in blood loss reduction among risk of postpartum hemorrhage vaginal deliveries - Vanitha, M.; Sujathasenthil, S.; Anandan, Heber (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: This study compares the efficacy of intramuscular oxytocin and oxytocin with sublingual misoprostol administration among the primary postpartum hemorrhage (PPH) mothers of vaginal deliveries. The aim is to compare the effectiveness of intramuscular oxytocin versus oxytocin with sublingual misoprostol in blood loss reduction among women at risk of PPH undergoing vaginal deliveries. Methods: Each group, 50 mothers were selected from the risk of PPH vaginal mothers in the labour ward of the study area. Results: The two groups’ mothers were not statistically significantly differed (P>0.05) in respect of their demographic and clinical variables such as age, gravida, risk factors, the onset of labour and type of delivery. The mean blood loss of group I was 315.4±111.4 ml and group II mean blood loss was 241.4±191.2 ml. The difference between the two groups’ blood losses was statistically significant (P<0.05). Conclusions: Oxytocin with sublingual misoprostol significantly reduced the blood loss during 3rd stage labour than only oxytocin administration.